Effect of Optimum Motor Relearning Programme on Hand Function of Stroke Patients - Jie CHEN; Fuchun WU; Guoqing MO; Debiao YU (康复学报)
Objective:To study the effect of optimum motor relearning programme (OMRP) on hand function of stroke patients with hemiplegia.Methods:56 stroke patients were divided into treatment group and control group by a random number table, and 28 patients in each group. The control group received routine rehabilitation therapy, and the treatment group received routine rehabilitation therapy and OMRP. The hand function of patients in the two groups was assessed by Wrist part of Fugl-Meyer Assessment Upper Extremity (FMA-UE), Motor Function Status Scale (MSS) and Modified Barthel Index (MBI) before and 4, 6, 8 weeks after treatment and a 3-month follow-up on the patients leaving hospital.Results:After 4, 6 and 8 weeks of treatment, FMA-UE and MBI of the two groups were increased significantly (P<0.05). After 6 and 8 weeks of treatment, MSS of the two groups was increased significantly (P<0.05). Whereas a 3-month follow-up on the patients leaving hospital, FMA-UE, MSS and MBI of the two groups did not show significant difference (P>0.05). After 4, 6 and 8 weeks of treatment, FMA-UE and MBI in the treatment group were increased significantly compared with the control group (P<0.05). After 6 and 8 weeks of treatment, MSS in the treatment group was increased significantly compared with the control group (P<0.05). A 3-month follow-up on the patients leaving hospital, FMA-UE, MBI and MSS in the treatment group were superior to those in the control group (P<0.05).Conclusion:Conventional rehabilitation therapy combined with OMRP can effectively improve the hand function of stroke patients.